Analisis SCP Industri E-Commerce Indonesia dan Dampaknya pada Kesejahteraan Konsumen : Penelitian - Khairani Matondang; Aqilah Apritia Parawanza; Jemelly Prisya Simanjuntak; Yolanda Tampubolon (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Using the Structure–Conduct–Performance (SCP) framework, this study aims to evaluate the structure, behavior, and performance of the Indonesian e-commerce industry, and to explain its impact on consumer welfare. The research method used is a descriptive qualitative approach. Stakeholders in this study consist of business competition regulators, e-commerce platform managers, micro, small, and medium enterprises (MSMEs), and consumers residing in the cities of Jakarta, Bandung, and Surabaya. To identify patterns related to the SCP dimensions, data were collected through observation, interviews, and review of industry documents. The results show that the Indonesian e-commerce market structure tends to be concentrated among a few large players that control significant market share. Intensive promotional strategies, integration of logistics and payment services, and utilization of data for personalization and algorithms are examples of companies' competitive behavior. These conditions result in market performance, which provides benefits to customers in the form of competitive prices, product variety, and ease of distribution. However, there are also risks, such as potential predatory practices, dependence on promotions, limited choice due to market consolidation, and data privacy. According to this study, although e-commerce in Indonesia offers short-term welfare benefits for consumers, digital competition oversight policies, algorithmic transparency, and support for MSMEs are needed to achieve a balance between innovation and consumer protection.